Narratives of decommunization in Ukraine’s cultural space - O. A. Grytsenko (Ukrainian Cultural Studies, 2019)
The article offers a cultural study of one of key aspects of the decommunization process in contemporary Ukraine, formally started by the introduction of so-called ‘four decommunization laws’ adopted on April 4, 2015, as manifested in the country’s cultural space through major narratives that describe, interpret and mythologize this process from various cultural and ideological positions and viewpoints. The methodological background for the study is provided by well-known cultural studies’ approach that, according to Paul Du Gay, Stuart Hall and others, presumes a systemic analysis of five key aspects of a given cultural phenomenon, namely, its production (creation), its consumption (reception), its regulation (by the state and other actors), its representations in culture (including narratives about it), and identities shaped or transformed by it. In this article, the penultimate part of a cultural study of Ukrainian decommunization is presented in detail. An overview of dozens of articles, columns, interviews and other texts about the decommunization in Ukrainian and foreign media demonstrates that there seem to be four main groups of decommunization narratives, tentatively named: the ‘purification of Ukraine’ narrative, the regional (or decentralized) narrative, the ‘Bandera-ization’ narrative, and the liberal narrative, each with its characteristic modes of emplotment (from epic romance to satire), with its civilization perspective, its set of symbols and values, its ‘heroes’ and ‘villains’. Unsurprisingly, those portrayed as heroes in affirmative narratives (that of ‘purification’, for instance) tend to become villains in negative narratives, the head of Ukrainian Institute of National Remembrance Volodymyr Viatrovych being the most prominent one.